2010
DOI: 10.1089/thy.2010.0072
|View full text |Cite
|
Sign up to set email alerts
|

WDR3Gene Haplotype Is Associated with Thyroid Cancer Risk in a Spanish Population

Abstract: These results indicate for the first time that WDR3 is a risk factor to thyroid cancer, suggesting its implication in the etiology of thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Previous studies conducted by our group in this region have found that the WDR3 gene, mapped in this region, shows a significant association with DTC, suggesting its implication in the aetiology of thyroid cancer [3].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Previous studies conducted by our group in this region have found that the WDR3 gene, mapped in this region, shows a significant association with DTC, suggesting its implication in the aetiology of thyroid cancer [3].…”
Section: Introductionmentioning
confidence: 57%
“…Aiming to find a reasonable explanation for the association observed between WDR3 polymorphisms and DTC incidence, we have already reported the up-regulation of WRD3 in different thyroid cancer cell lines, suggesting its possible implication in thyroid cancer tumorigenesis [3]. This would agree with the studies carried out in the breast carcinoma cell line MCF-7 showing that the suppression of WDR3 reduce cell proliferation, decrease cell size and reduce foci formation, indicating that WDR3 confers a growth and proliferative advantage on cancer cells [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these regions contain thyroid differentiation genes FOXE1 and NKX2-1, respectively (4,5). Additional polymorphisms at 5q33 and 1p12 are also susceptibility loci for thyroid cancer (6,7), and more recently, the WDR3 gene that maps at 1p12 was found to be associated with the disease (8). In chromosome 8q24, three independent regions have been related to risk of different types of cancers, including thyroid cancer, but no known genes reside in that susceptibility region (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, several genetic studies have reported relationship between PTC and candidate genes, such as WD repeat domain 3 (WDR3) (25), vascular endothelial growth factor A (VEGFA) (26), RAD52 homolog (S. cerevisiae) (RAD52) (27), protein tyrosine phosphatase, receptor type, J (PTPRJ) (28), purinergic receptor P2X, ligand-gated ion channel, 7 (P2X7) (29), interleukin 6 (interferon, beta 2; IL6) (30), IL10 (31) and IL11 (32). …”
Section: Discussionmentioning
confidence: 99%